2007
DOI: 10.1016/j.chom.2007.03.002
|View full text |Cite
|
Sign up to set email alerts
|

The Stoichiometry of Antibody-Mediated Neutralization and Enhancement of West Nile Virus Infection

Abstract: Antibody binding to the icosahedral arrangement of envelope proteins on the surface of flaviviruses can result in neutralization or enhancement of infection. We evaluated how many antibodies must bind to a given epitope on West Nile virus (WNV) to achieve neutralization. The most potent monoclonal antibodies (mAbs) block infection at concentrations that result in low occupancy of accessible sites on the virion, with neutralization occurring when as few as 30 of 180 envelope proteins are bound. In contrast, wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
449
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(474 citation statements)
references
References 63 publications
22
449
1
2
Order By: Relevance
“…Fourth, Ab-mediated neutralization of viruses from the Flaviviridae family requires a stoichiometric Ab binding that exceeds a certain threshold (35)(36)(37). This threshold was estimated to be up to 30 Ab molecules per virion for West Nile virus (53,54) and is represented in our model with the relation u i,j = v K j,i between the probabilities u i,j and v j,i of neutralization and immune stimulation. The neutralization effectiveness of the Ab may be further hampered by dilution with low-affinity Abs resulting from boosting of different memory B cells by a viral variant or from polyclonal antigen-independent activation of naive B cells by HCV (55).…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, Ab-mediated neutralization of viruses from the Flaviviridae family requires a stoichiometric Ab binding that exceeds a certain threshold (35)(36)(37). This threshold was estimated to be up to 30 Ab molecules per virion for West Nile virus (53,54) and is represented in our model with the relation u i,j = v K j,i between the probabilities u i,j and v j,i of neutralization and immune stimulation. The neutralization effectiveness of the Ab may be further hampered by dilution with low-affinity Abs resulting from boosting of different memory B cells by a viral variant or from polyclonal antigen-independent activation of naive B cells by HCV (55).…”
Section: Discussionmentioning
confidence: 99%
“…47 The JEV SA14-14-2 RVPs expressing green fluorescent protein (GFP) were produced in HEK 293T cells, as described previously. 47,50,51 The RVP titers were determined by serial dilution of JEV RVP stocks and infecting Raji cells in 96-well plates. The RVP-infected cells were fixed with paraformaldehyde and the percentage of GFP expressing cells was determined by flow cytometry.…”
Section: Cellsmentioning
confidence: 99%
“…Previous studies have suggested that Abs can neutralize flaviviruses at a stoichiometric threshold of~30 bound Abs (14). Given a series of M uncorrelated states of the Ab-virus complex, and counting the number of states, k, where N bound < 30; the ratio k/M is a measure of infectivity, whereas (M -k)/ M provides a measure of neutralization; these measurements can be used to compute theoretical neutralization or infectivity curves.…”
Section: Ab Boundð½abþmentioning
confidence: 99%
“…This stoichiometric threshold of~30 Abs corresponds to the coating theory of neutralization (12,15,16), which postulates that a threshold density of Abs bound, as a function of virus surface area, is sufficient for neutralization and predicts that flaviviruses, with a surface area of~7000 nm 2 , should be neutralized by~20-50 Abs. Subsequent experiments have shown that subneutralizing Ab binding stoichiometries facilitate antibody-dependent enhancement of infection (14), underscoring the critical role of antibody binding stoichiometry on flavivirus immunity and pathogenicity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation